Ontology Design Of A Modern Learning Environment And Modern Pedagogy Using Protégé Software - S. Auna, Hariyanto; Prasetya, Noven Indra; Surur, Agus Miftakus; Ulfa, Saida; Soepriyanto , Yerry; Salleh , Shaharuddin Md (LP2M Institut Agama Islam Negeri (IAIN) Kediri, 2024)
This article discusses ontology design for modern learning environments and modern pedagogy using Protégé software. Library research methodology is used to formulate an ontology that reflects the structure, relationships and properties of modern learning entities. This ontology serves as a formal representation that allows a better understanding of the essential elements in modern learning and the relationships between them. The ontology approach provides a clear framework for designing and developing adaptive and responsive learning environments, as well as for designing teaching strategies that suit individual needs. By using Protégé, researchers can systematically describe key concepts in modern learning, including collaborative learning methods, technology integration, and personalized learning. The results show that the resulting ontology can be a useful tool for curriculum developers and teachers to design learning experiences that are more effective and relevant to current demands.